System analysis of the world cryptocurrency market - Merkulova, T. V.; Masliy , J. M. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The main focus of this article is the analysis of the global cryptocurrency market as an integrated system of cryptocurrencies and infrastructures that ensure their functioning. In particular, the general state of the cryptocurrency market and its current trends have been considered. The main part of the analysis was conducted on the structure of the global cryptocurrency market and its main components. Based on the indicator of cryptocurrency market capitalization, leading cryptocurrencies have been defined. They currently represent 80% of the world cryptocurrency market. These include Bitcoin, Ethereum, Ripple, Bitcoin Cash, Cardano, Litecoin and NEM. Key players in the cryptocurrency market infrastructure have been also determined, they support and contribute to the development of the market of almost every cryptocurrency. These include miners, full nodes, exchanges, wallets and payment companies. The main market indicators for each leading cryptocurrencies such as: the market share and its change over the year, the degree of influence of the cryptocurrency on the state of the global market, the dynamics of prices and their volatility have been analyzed. The infrastructure of the market of each cryptocurrency has been estimated on the basis of indicators of the reliability of the infrastructure and its trade opportunities. The study showed a high growth rate of Bitcoin and along with it a number of significant altcoins over the past year, which had a favorable effect on the state of the common cryptocurrency market. Almost every cryptocurrency showed positive trends. Ripple is the absolute record holder of price growth over the past year, followed by NEM. Bitcoin and Ethereum are the least financially risky ones in terms of volatility. In addition, Ethereum has the most reliable infrastructure, and Bitcoin has the most secured by exchanges and wallets. Cardano showed the highest growth rates in a short period of time. In general, these phenomena are positive forerunners for the cryptocurrency industry.